Active site regulated Z-scheme MIL-101(Fe)/Bi2WO6/Fe(iii) with the synergy of hydrogen peroxide and visible-light-driven photo-Fenton degradation of organic contaminants. Issue 18 (27th April 2022) - Song, Rutong; Yao, Jun; Yang, Mei; Ye, Zhongbin; Xie, Zhuang; Zeng, Xiang
Abstract : The band structure analysis shows that BWO and MIL-101(Fe) is typical type-II scheme, which provokes that the photogenerated carriers will transfer from a more positive position to a more negative position. The Z-scheme heterojunction is proposed. Abstract : Water pollution control is one of the major challenges currently faced. With the development of photocatalytic technology, an increasing number of new and efficient catalysts have been developed, but most of the catalysts have limited light capture ability and catalytic degradation efficiency. Therefore, in this work, hydrogen peroxide was further introduced to establish a photo-Fenton system to improve the photocatalytic effect by constructing a Z-scheme, and the degradation ability of the catalyst was maximized. Moreover, we successfully adhered bismuth tungstate nanosheets onto the surface of a MIL-101(Fe) framework and changed the number of active sites with iron ions of different doping amounts. We found that the number of active sites in the photo-Fenton system does not increase linearly, but increases and decreases regularly, which is similar to the change in band structure after doping. In addition, the results of the radical scavenger experiment and electron paramagnetic resonance (EPR) revealed that both hydroxide radical (˙OH) and superoxide radical (˙O2 − ) participated in methylene blue (MB) degradation, of which ˙OH was the main active species for pollutant degradation. Based on high-performance liquid chromatography-mass spectrometry (HPLC-MS) analysis, the possible degradation pathways were proposed. We believed that this work will provide insights into the heterojunction photo-Fenton system.